Convergent evolution of flightlessness in rails (Aves: Rallidae) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Evolutionary Ecology at Massey University, Manawatū, New Zealand - Gaspar, Julien (Massey University, 2022)
Different species can independently evolve similar phenotypic traits in response to the same environmental challenges. The resulting convergence of traits shows how environmental circumstances that apply selective pressure on the genomes of different lineages can result in analogous adaptations. A remarkable example of this evolutionary process is the secondary loss of flight in birds which repeatedly occurs in avian diversification. Flightlessness in bird species have been encountered on many oceanic islands and is interpreted as an effect of the insular condition that often provides a habitat with few or no predators, reduced competition for resources, and the opportunity to forage without flying. The rails or Rallidae are an exceptional avian family to study the evolution of flightlessness as among the 130 extant species, 30 have independently lost the ability to fly. In this research, genomic and morphological data were integrated to compare traits of volant and flightless species in a phylogenetic context and to investigate the evolutionary processes involved in the loss of flight. First, morphological and phylogenetic data were used to compare species with and without the ability to fly in order to determine whether major phenotypic effects of the transition from volant to flightless are shared among lineages. Second, genome assemblies were generated for representatives of four rails: two volant and two flightless species. Then, a genome-wide comparison of coding regions from volant and flightless rails was performed to detect genetic regions associated with the flightless trait. The newly assembled and annotated genomes showed differences in heterozygosity between flightless and volant species with lower heterozygosity in flightless species that probably reflects their relatively small populations. I found statistical support for similar morphological responses among unrelated flightless lineages, characterised by a shift in energy allocation from the forelimbs to the hindlimbs. Flightless birds exhibited smaller sterna and wings than volant taxa in the same family along with wider pelves and more robust femora. Phylogenetic signal tests showed that those differences were independent of phylogeny and instead demonstrated convergent morphological adaptation associated with a walking ecology. Evidence of different selective pressures between species with and without the ability to fly was detected in hundreds of genes. This included relaxed, intensified, and positive selection in flightless species as well as evolutionary rate differences of genes in volant and flightless taxa and proteins carrying function-altering amino acid changes in the flightless rails. Genes associated with flightlessness were enriched in biological functions that aligned well with the ability to fly such as muscle, bone, limb, and heart development. However, other enriched functions were not directly linked to flying and may result from the ecological consequences of flightlessness; these included the immune system, renal functions, lipid metabolic system, cognition, and the sensory system. Finally, many genes under selective pressures in flightless species were involved in gene regulation and post-translational modification. This suggests that genetic adaptations to flightlessness are not only found in important developmental genes but also in patterns of gene expression and protein modifications. This study presents reliable methods to generate genomic data and to use it to assess the selective pressures involved in a convergent phenotype.
Keywords: Rails (Birds); Flightless birds; Evolution; Convergence (Biology); 310410 Phylogeny and comparative analysis